BENTUK DAN MAKNA: HASEIGO BERIMBUHAN -GIMI: PENDEKATAN MORFOSEMANTIK - Nani Sunarni (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This study focuses on the word derivation or haseigo which has the affix -gimi. The data used in this research are sentences containing derivational words with the suffix -gimi. The data source is the YouTube channel Nihongo no Mori. This study aims to identify the form and meaning of haseigo with the suffix -gimi. In form, the suffix -gimi is attached to verbs and nouns which are negative emotional words and forms the adjective -na. In terms of meaning, it is identified that sufik -gimi expresses the characteristic, condition of feelings resulting from significant changes in a person or expresses a tendency towards a condition or feeling of a person that is subjective and temporary.